(untitled) (Comparative & International Education Series, 2022)
Having insights into returning graduates’ employability in their home country has become critical given that a majority of international graduates choose to head home after their overseas study. However, there is a paucity of the positioning and re-positioning of international graduates in their home labour market, especially those who work as English teachers. To address this critical gap, this study interviewed eight Vietnamese English teachers who used to sojourn for their further education at the Masters or PhD levels outside Vietnam. The findings show that although the returnee teachers experienced some barriers and constraints, they successfully navigated the domestic labour market to adapt and advance their career development. This study brings more insights into international graduate employability in Vietnam, which has experienced a marked shift in the labour market. Important implications are provided for returnees and home employers to facilitate returnees’ re-integration to the local market. How to cite in APA: Pham, L. T. T, & Phan, A. N. Q. (2022). Coming Home: Internationally-trained Vietnamese English language teachers’ perceived employability. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 123-144). STAR Scholars. [order hardcopy ]